STATUS OF ARTISANAL FISHING TRAPS USED BY FISHERFOLKS IN SELECTED FISHING COMMUNITIES IN EPE LAGOON, NIGERIA - AKINNIGBAGBE, R. O (Nigerian Journal of Fisheries, 2018)
The study evaluates the status of artisanal fishing traps and its operational techniques employed by fisherfolks in four fishing communities in Epe Lagoon. The objective is to have an in-depth understanding of trap fishing within the communities, so as to know the challenges faced by the fisherfolks and recommend (if possible) more efficient fishing traps to enhance their fishing activities and increase productivity. The big and small cylindrical basket traps were preferred by the fisherfolks because of the catches obtained from these traps. Traps are mostly used in the shallow depth of water between 1-2 meters as indicated by 69% of the respondents and 78% of the respondents prefer operating the fishing traps at either between 4-6am or 4-6pm at all the selected fishing communities. Despite the various methods of trap managements in Epe Lagoon, most of the traps used are not durable and the availability of the materials for constructing these traps are not easily accessible by the artisanal fisherfolks. There is a need to modify the traditional fishing traps with more durable and available materials for better performances. Keywords: , , , ,